Research and development investment and board characteristics - Ahlem Selma Messai; Fathi Jouini (Cogent Business & Management)
This study examines the impact of board characteristics on Research and Development (R&D) investment decisions in 102 French companies from 2010 to 2021. Employing generalized least squares, the Newey-West estimator, and weighted least squares methods, we comprehensively analyze the relationships between board size, independence, gender diversity, meeting frequency, CEO duality with R&D expenditure. Our findings highlight significant associations between certain board characteristics and R&D investment. Specifically, smaller boards, gender-diverse boards, and more frequent board meetings positively correlate with R&D spending, underscoring the role of diverse perspectives and active board engagement in fostering innovation. Moreover, our study integrates multiple econometric techniques, reinforcing the robustness of our findings. We reveal the importance of board composition in shaping strategic decisions regarding R&D investment, offering nuanced insights into their influence in the French context. Our results emphasize the critical role of corporate governance structures in driving R&D investment behavior, contributing to firms’ long-term performance and competitiveness through enhanced innovation and knowledge development.